INVESTIGATION OF CHEMICAL COMPOSITION FROM DRYOPTERIS CHOCHLEATA (D.DON) C. CHR. (DRYOPTERIDACEAE) - Dubal, Kanchan; Patil, Sachin; Dongare, Meena; Kale, Manisha (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: The present study was for the determination of bioactive volatile compounds from chloroform and ethanolic extract. Methods: For present investigation of the samples were carried out by using Shimadzu Make QP-2010 with nonpolar 60 M RTX 5MS Column. Interpretation on Mass-Spectrum GC-MS was conducted using the database of National Institute Slandered and Technology (NIST) having more 62,000 patterns. Results: In Ethanolic extract seven compounds and chloroform extract fourteen compounds were identified. The common compounds in these two extracts are Germacrene D; 1, 3-cyclohexanedione, 2-methyl-2 (3-Oxobutyl); Neoisolongifolene, 8, 9-dehydro. Coclusion: Present investigation emphasizes the efficacy of traditional remedies and that it inspires the people to realize the importance of natural resources for its potent pharmaceutical use. Keywords: Medicinal pteridophyte, Gas chromatography-mass spectroscopy analysis, Ethanol extract, Chloroform extract, Bioactive compounds.